A controlled trial of dissemination and implementation of a cardiovascular risk reduction strategy in small primary care practices. (13th October 2020) - Cykert, Samuel; Keyserling, Thomas C.; Pignone, Michael; DeWalt, Darren; Weiner, Bryan J.; Trogdon, Justin G.; Wroth, Thomas; Halladay, Jacqueline; Mackey, Monique; Fine, Jason; In Kim, Jung; Cene, Crystal
Abstract: Objective: To assess the effect of dissemination and implementation of an intervention consisting of practice facilitation and a risk‐stratified, population management dashboard on cardiovascular risk reduction for patients at high risk in small, primary care practices. Study Setting: A total of 219 small primary care practices (≤10 clinicians per site) across North Carolina with primary data collection from electronic health records (EHRs) from the fourth quarter of 2015 through the second quarter of 2018. Study Design: We performed a stepped‐wedge, stratified, cluster randomized trial of a one‐year intervention consisting of practice facilitation utilizing quality improvement techniques coupled with a cardiovascular dashboard that included lists of risk‐stratified adults, aged 40‐79 years and their unmet treatment opportunities. The primary outcome was change in 10‐Year ASCVD Risk score among all patients with a baseline score ≥10 percent from baseline to 3 months postintervention. Data Collection/ Extraction Methods: Data extracts were securely transferred from practices on a nightly basis from their EHR to the research team registry. Principle Findings: ASCVD risk scores were assessed on 437 556 patients and 146 826 had a calculated 10‐year risk ≥10 percent. The mean baseline risk was 23.4 percent (SD ± 12.6 percent). Postintervention, the absolute risk reduction was 6.3 percent (95% CI 6.3, 6.4). Models considering calendar time and stepped‐wedge controls revealed most of the improvement (4.0 of 6.3 percent) was attributable to the intervention and not secular trends. In multivariate analysis, male gender, age >65 years, low‐income (<$40 000), and Black race ( P  < .001 for all variables) were each associated with greater risk reductions. Conclusion: A risk‐stratified, population management dashboard combined with practice facilitation led to substantial reductions of 10‐year ASCVD risk for patients at high risk. Similar approaches could lead to effective dissemination and implementation of other new evidence, especially in rural and other under‐resourced practices. Registration: ClinicalTrials.Gov 15‐0479.